The right of the child to be heard in the Croatian family law system - Šimović, Ivan (European Integration Studies, 2023)
Croatian family law system positions children as legal subjects who can actively participate and make autonomous decisions in proceedings in which their rights and interests are decided. This is because children are holders of many substantive rights which are of little or no value if they cannot be realized in practice. Therefore, the Croatian legislator tried to ensure a system of procedural rights of the child authorizing them to protect their rights in all judicial and administrative proceedings either directly or, usually, through a legal representative. Pivotal procedural right of the child recognized by national and international sources of law is the right to be informed and heard in all matters affecting him/her. Hence, adequate understanding and implementation of this procedural right in the Croatian legislative and judicial system is essential. The goal of this article is to present a comprehensive analysis of relevant Croatian legislation, judicial practice, academic literature, and research studies in the context of the realization of the child’s right to be informed and heard, as well as to point out the deficiencies which show that the Croatian family law system is yet to function perfectly in practice.